Cytotoxic metabolites from the endophytic fungus Chaetomium globosum 7951. Issue 28 (21st May 2019) - Wang, Fang; Zhao, Wuli; Zhang, Conghui; Chang, Shanshan; Shao, Rongguang; Xing, Jianguo; Chen, Minghua; Zhang, Yixuan; Si, Shuyi
Abstract : Demethylchaetocochin C and chaetoperazine A, two new epipolythiodioxopiperazine alkaloids, and three known analogs were isolated from Chaetomium globosum 7951. Demethylchaetocochin C significantly inhibits human lung cancer cell growth. Abstract : The following compounds were isolated from acetate extracts of Chaetomium globosum 7951 solid cultures: demethylchaetocochin C (1 ) and chaetoperazine A (3 ), two new epipolythiodioxopiperazine (ETP) alkaloids, a novel pyridine benzamide, 4-formyl- N -(3′-hydroxypyridin-2′-yl) benzamide (6 ), and three known ETP derivatives (2, 4, and5 ). The structures of these compounds were determined using extensive spectroscopic data analysis. Compounds1–3, and6, inhibited the growth of MCF-7, MDA-MB-231, H460 and HCT-8 cells with an IC50 of 4.5 to 65.0 μM.